HUBUNGAN ANTARA KESELAMATAN DAN KESEHATAN KERJA (K3) DENGAN KINERJA KARYAWAN PADA PT FRISIAN FLAG (PLANT PASAR REBO), JAKARTA - dedy syahyuni (Universitas Bina Sarana Informatika, 2017)
Abstract Work health and safety is one of important thing that every company need to take concern, especially if employee work with big machine and more specific for employee that work in production department. With good work health and safety management, company will be able to improve the performance of employee. This paper try to analize the relationship between two variable (work health and safety with performance) and the respondents are employee from PT Frisian Flag (plant Pasar rebo). Form the calculation of the obtain result: There is a positive relation between two variables (work health and safety with performance) with correlation 0,583 and R square 34 %.Keyword: production, work performance, work safety.